Identification and characterization of peat soils using a physiographic approach at semi-detailed scale: a case study in Bangka Belitung Islands Province, Indonesia - Sukarman Sukarman; Yiyi Sulaeman; Edi Yatno; Rachmat Abdul Gani; Budiman Minasny (Universitas Sebelas Maret, 2024)
Understanding peatland coverage and characteristics is essential for improved utilization and conservation efforts. Peatlands in Bangka Belitung Islands, Sumatra, are under threat of illegal mining activities. Creating detailed maps is challenging in Indonesia amid low accessibility, yet the physiographic approach provides an alternative strategy in peatland map provision. This research aims to update peat data in the Bangka Belitung Islands Province, create peat soil maps at a scale of 1:50,000, and estimate peat soil carbon stocks. This research started with a base map using a 1:50,000 scale, surveyed and sampled the soil on transects perpendicular to the river, analyzed the samples in the laboratory, and created a peat soil map. Compared with the existing map, the new map improves land unit attributes and peat characteristics as well as improves delineation results. Results show that peat soils cover 24,311 hectares, mostly distributed in Central Bangka and South Bangka Regencies, with depths varying between 50 to < 300 cm. Shallow peats dominate with an area of 13,668 hectares (56.22%). The estimated carbon stock contained in peat is 11.6 million tons C. The peat soils are Organosol Saprik, Organosol Hemik, and Organosol Sulfidik. The soils are acidic with low exchangeable cations and base saturation. The study highlights that deep peat soils under bushes and shrubs should be conserved for forests or reforested. Detailed spatial information on peatlands is useful for policymakers related to local peat soils planning and management.